Agricultural practices in the properties of the participants of the Inconfidencia Mineira (Minas Gerais, district of Rio das Mortes, 2nd half of the 18th century) - Rodrigues, Andre Figueiredo [UNESP]; Aguiar, Jose Otavio (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2019)
The article analyzes the agricultural practices evidenced in the properties of the participants of the Inconfidencia Mineira, residents in the district of Rio das Mortes, south of the captaincy of Minas Gerais, in the second half of the 18th century. To this end, they examine the production of rice, beans and corn found in those farms, revealing the food supply and the data of local production.
Keywords: Food production; Agriculture; Minas Gerais; District of Rio das Mortes; 2nd half of the 18th century